2001
DOI: 10.1002/gcc.1189
|View full text |Cite
|
Sign up to set email alerts
|

Novel evidence of a role for chromosome 1 pericentric heterochromatin in the pathogenesis of B‐cell lymphoma and multiple myeloma

Abstract: 1q rearrangement is a remarkably frequent secondary chromosomal change in both non-Hodgkin's lymphoma (NHL) and multiple myeloma (MM), where it is associated with tumor progression. To gain insight into 1q rearrangement-associated disease mechanisms, we used fluorescence in situ hybridization (FISH) to search for recurring 1q breaks in 35 lymphoma samples (31 NHL patients and 4 lymphoma-derived cell lines) as well as 22 MM patients with cytogenetically determined 1q abnormalities. Strikingly, dual-color FISH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 62 publications
3
86
0
Order By: Relevance
“…16,[19][20][21][22][23][24] The molecular structure of the t(8;14;18) rearrangement has been studied in detail in the cell lines DOHH2, VAL and ROS-50. 5 These studies have demonstrated that concurrent deregulation of BCL2 and MYC was achieved by translocation with a single IGH allele, whereby separation of the 3 0 and 5 0 IGH enhancer elements occurs with relocation of the BCL2-5 0 IGH enhancer fusion to the der (8), and translocation of MYC adjacent to the 3 0 IGH enhancer element that is retained on the der (14).…”
Section: Discussionmentioning
confidence: 99%
“…16,[19][20][21][22][23][24] The molecular structure of the t(8;14;18) rearrangement has been studied in detail in the cell lines DOHH2, VAL and ROS-50. 5 These studies have demonstrated that concurrent deregulation of BCL2 and MYC was achieved by translocation with a single IGH allele, whereby separation of the 3 0 and 5 0 IGH enhancer elements occurs with relocation of the BCL2-5 0 IGH enhancer fusion to the der (8), and translocation of MYC adjacent to the 3 0 IGH enhancer element that is retained on the der (14).…”
Section: Discussionmentioning
confidence: 99%
“…Pericentromeric rearrangements of Chr1 and Chr16 are overrepresented in diverse types of cancers, including hepatocellular carcinomas and Wilms tumors, and generally lead to gains of 1q and/or losses of 16q (Brito-Babapulle and Atkin, 1981;Le Baccon et al, 2001;Mitelman et al, 2001). In a study of hepatocellular carcinomas by comparative genomic hybridization, 23 out of the 36 tumors examined showed 1q gain; 22 of these displayed Chr1 Sat2 hypomethylation at BstBI sites (Wong et al, 2001).…”
Section: Hypomethylation Of Single-copy Genes In Cancermentioning
confidence: 99%
“…β-catenin nuclear translocation has been identified as a key event that disturbs Wnt/β-catenin signaling and BCL-9, an extremely essential coactivator of the β-catenin-TCF complex and a novel therapeutic target (24,25). Our results show that, the ectopic expression of PCDH10 can hinder the protein expression of β-catenin and restrain its nuclear translocation as well as the expression of BCL-9.…”
Section: Discussionmentioning
confidence: 60%
“…Of note, the human BCL-9 gene, which was first identified by cloning the t(1;14)(q21;q32) translocation from a patient with B-cell acute lymphoblastic leukemia, has been identified as a critical coactivator of β-catenin activation in association with LEF/TCF family members. It has been confirmed that BCL-9 possesses a potent transcription activation domain, which is crucial for BCL-9 to promote β-catenin translocation and aberrant transcription of Wnt target genes, which in turn promotes tumor cell proliferation, disease progression and drug resistance (23)(24)(25). Those findings emphasize the importance of this pathway and BCL-9 for identification of appropriate target drugs.…”
Section: Introductionmentioning
confidence: 87%